OPTIMALISASI LAHAN KURANG PRODUKTIF SEBAGAI GREEN CORNER UNTUK PEMBERDAYAAN DAN KETAHANAN PANGAN WARGA PANDANSARI KABUPATEN KEDIRI - Prima Ayu Rizqi Mahanani; Athallah Aris Bahtiar; Ilham Ramadhan; Alif Akbar Maulana; Muhammad Najwa Fikri; Mananda Asrul Ramandika; Revita Putri Amelia; Sri Wahyuningsih Puspita Dewi; Jazila Zulfa Zahra (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
. Pandansari Village, Kediri Regency has a lot of unproductive land that has not been optimally utilized to support community food security. This community service program aims to optimize this land into a green corner as a means of empowering and strengthening local food security through an Asset-Based Community-Driven Development (ABCD) approach. The ABCD method is implemented through five stages, namely: discovery (identifying potential), dream (formulating a shared vision), design (designing strategies), define (setting priorities), and destiny (implementation and evaluation) involving field observations, interviews, focus group discussions, and planting implementation. The program results show the transformation of unproductive land into a productive green corner with the cultivation of various vegetables (chili, eggplant, tomato, corn, basil, kale) and medicinal plants (ginger, turmeric, lemongrass, galangal, laos, rosella, purple leaves, kaffir lime) as well as ornamental flowers and supporting structures. This program successfully involved PKK mothers as the main managers with the full support of village officials so that the green corner not only functions as an alternative food source and educational facility, but also increases household economic independence and the welfare of the Pandansari Village community in a sustainable manner.